Antioxidant effects of vitamin D on lacrimal glands against high dose radioiodine-associated damage in an animal model. (2nd January 2019) - Eksioglu, Umit; Atilgan, Hasan Ikbal; Yakin, Mehmet; Yazihan, Nuray; Altiparmak, Ugur Emrah; Yumusak, Nihat; Korkmaz, Meliha; Demir, Ayten; Ornek, Firdevs; Aribal Ayral, Pelin; Koca, Gokhan
Abstract: Purpose: To evaluate antioxidant effects of active vitamin D (calcitriol) against high-dose radioiodine (RAI) therapy-associated damage of lacrimal gland. Materials and methods: Wistar albino rats were used and divided into three groups randomly ( n = 12/group). The first group was appointed as the negative control group and received no RAI or medication. The second group was appointed as the positive control group that only received 3 mCi/kg (111 MBq/kg) RAI via gastric gavage and the last group was the treatment group that received 3 mCi/kg RAI via same method and calcitriol (200 ng/kg/day) via intraperitoneal administration. Seven days after RAI administration, bilateral intraorbital (IG), extraorbital (EG) and Harderian (HG) glands were removed for the evaluations of histopathologic, tissue cytokine, total oxidant status (TOS) and total antioxidant status (TAS). Results: RAI led to significant increase in tissue TOS, TNF-α, IL-6 levels and significant decrease in IL-10 and TAS levels ( p < 0.05 for each). Addition of adjunctive calcitriol reversed all these parameters significantly ( p < 0.05 for each).The following histopathologic parameters were seen more frequently in positive control group than the other groups: Abnormal lobular pattern, perivascular infiltration, periductal infiltration, lipofuscin-like accumulation, acinar atrophy, periductal and periacinar fibrosis in all lacrimal gland types ( p < 0.05), acinar fibrosis in EG ( p = 0.049), periductal fibrosis in EG and HG ( p = 0.049 and 0.038, respectively), abnormal cell outlines in EG and HG ( p = 0.020 and 0.011, respectively) and variation in cell size in the IG and the HG ( p = 0.003 and 0.049 respectively). Conclusions: RAI caused significant oxidative stress and inflammation in lacrimal glands. Vitamin D demonstrated potent anti-inflammatory, antioxidant and radio-protective effects on lacrimal glands in histopathologic, tissue cytokine and oxidant/antioxidant level evaluations.